2006
DOI: 10.1080/01674820500490218
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic nervous system activity in the late luteal phase of eumenorrheic women with premenstrual symptomatology

Abstract: The majority of women of reproductive age experience a regular recurrence of various symptoms in the premenstrual phase. The etiopathogenesis of premenstrual symptomatology, however, remains inconclusive. The present study was proposed to evaluate whether the activity of the autonomic nervous system (ANS), which largely contributes to the relative stability of a human's internal environment, is altered during the menstrual cycle of women with premenstrual symptomatology. Thirty eumenorrheic young women partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 34 publications
3
68
1
Order By: Relevance
“…Similar to our findings, Matsumoto et al (13) found that heart rate was increased and HF power was decreased during the late-luteal phase compared with the follicular phase in women who scored high on a premenstrual distress questionnaire. HF power did not vary between menstrual phases in women who had a low score on the questionnaire (13). In contrast to our findings, another study found no change in HRV between the follicular and luteal phases in women diagnosed with PMDD.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar to our findings, Matsumoto et al (13) found that heart rate was increased and HF power was decreased during the late-luteal phase compared with the follicular phase in women who scored high on a premenstrual distress questionnaire. HF power did not vary between menstrual phases in women who had a low score on the questionnaire (13). In contrast to our findings, another study found no change in HRV between the follicular and luteal phases in women diagnosed with PMDD.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings in the control group that menstrual phase did not influence HRV during sleep support those of some previous studies that have investigated resting HRV in young women when awake (13,19). Others, however, have reported an increase in the LF/HF ratio in the luteal phase (14-16), which we did not find.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…24 The participants were also instructed to abstain from alcohol use and excessive physical activity for 24 hours before testing. 25,26 Referring to a study by Kiecolt-Glaser and colleagues 27 and the authors' own recent research on aromatherapy, 26 the olfactory function test was performed on all participants to confirm that none had anosmia. Briefly, participants were given two sets of three bottles-two held distilled water, and the third contained essential oils (yuzu or lavender)-and were asked to choose the one that differed from the other two.…”
Section: Participantsmentioning
confidence: 99%